Digital Game-Based Technology for English Language Learning in Preschools and Primary Schools: A Systematic Analysis - Ongoro, Catherine Akoth; Fanjiang, Yong-Yi (IEEE transactions on learning technologies, 2024)
This study aims to provide a systematic review of existing research on the use of digital game-based learning (DGBL) technology for foreign language (English) in preschool and elementary schools. Digital game-based technology enables learning to become more interactive and inspirational, thereby enhancing language acquisition. The authors present a DGBL classification schema with four main components, design principles, language content, pedagogical factors, and feedback mechanisms, as guidelines for designing and implementing DGBL in foreign language learning. This survey classifies and filters 110 published articles from January 2010 to April 2022 based on the proposed DGBL schema adhering to the insertion and omission criteria, from which 50 studies focus on preschool and primary school students between the ages of 2 and 10 years. The findings indicate that DGBL influences motivation, creativity, and problem-solving ability. However, the synthesized literature also reveals challenges and issues in designing and developing DGBL systems based on novel technologies. The findings are fundamental for exploring the game classification schema for designing and implementing game-based learning to augment the trends of DBGL in foreign language learning and identify the possible issues and solutions for DGBL to lessen health concerns and technology challenges. The authors recommend emerging technologies and software engineering processes as possible solutions for continuity in DGBL research by enlightening the significance of evolving technologies such as artificial intelligence, blockchain, deep learning, AR/VR, and DevOps.